The Relationship Between Emotion Regulation and Dysmenorrhea Intensity Pain in Adolescent Girls at SMAN 3 Malang - Dela Amalia Pridantara Putri; Shinta Wahyusari; Mokhtar Jamil (Jurnal Keperawatan Priority, 2026)
One of the significant physical changes experienced by adolescent girls is menstruation. Almost every adolescent girl experiences a menstrual disorder, namely dysmenorrhea. Dysmenorrhea is a gynecological disorder caused by an imbalance of the hormone progesterone in the blood, resulting in excessive prostaglandin production that triggers pain during menstruation. The intensity of dysmenorrhea can vary from mild, moderate, to severe. In addition to physical effects, menstrual pain may also cause psychological symptoms, such as uncontrolled emotions. With good emotion regulation, adolescent girls are able to manage, control, and express their emotions appropriately according to their menstrual condition. The purpose of this study was to determine the relationship between emotion regulation and the intensity of dysmenorrhea pain in adolescent girls at SMAN 3 Malang. This study used a quantitative method with a correlational approach and a cross-sectional design. Data were collected using questionnaires distributed via Google Form. The study involved 244 respondents who were students of SMAN 3 Malang in grades X, XI, and XII. Data analysis was conducted using the Spearman test. The results showed a p value of 0.002 (α< 0.05) with a correlation coefficient of r=-0.194. These findings indicate a significant negative relationship between emotion regulation and dysmenorrhea pain.